Critical discourse analysis on local cultural content in English textbooks - Fitri Handayani; Mike Amelia (ENGLISH EDUCATION DEPARTMENT - UNIVERSITAS SINGAPERBANGSA KARAWANG, 2023)
Local cultural representations can be found in textbooks as visual and textual artifacts. Local culture is shown in the book in an unique way as a cultural exhibition. The goal of this research is to investigate at how local culture is depicted in textbooks. The focus of the study is exploring the local content of cultural of an EFL textbook using critical discourse analysis as a methodological technique. The information was obtained from the “Headline English 2” English Textbook for the VIII grade (2018). The findings show that the cultural component of Indonesia was deliberately chosen to be included in this textbook in order increasing both teachers’ and students’ understanding of the language and culture interdependent relationship.